Evaluation of environmental support systems and their social psychological effects on weight management for combat sports student-athletes in higher education institutions - Yulin Li; Syed Kamaruzaman Syed Ali; Ahmad Zabidi Abdul Razak* (Environment and Social Psychology, 2026)
Combat sports are defined by strict weight classification systems, rendering weight management a pivotal factor influencing athletes’ competitive performance and long-term health outcomes. College student-athletes in combat sports confront unique predicaments stemming from their dual roles as students and athletes, navigating the competing demands of academic workloads, intensive athletic training, and ongoing physical development. While environmental support systems and socio-psychological factors are widely acknowledged as key determinants of health-related behaviors, their integrated impacts on weight management within this specific population remain underexplored. This study aimed to evaluate the current state of environmental support systems for weight management among college combat sports student-athletes and unpack the socio-psychological mechanisms through which these systems shape weight management behaviors and effectiveness. A mixed-methods research design was employed, combining quantitative questionnaires and qualitative in-depth interviews. Quantitative data were collected from 278 college combat sports student-athletes across 10 higher education institutions and analyzed using SPSS and AMOS for descriptive statistics, correlation analysis, and structural equation modeling. Qualitative data were gathered through in-depth interviews with 18 student-athletes and 6 coaches, processed via thematic analysis with Nvivo. The findings identified three core dimensions of environmental support systems (interpersonal, resource, and institutional support), with an overall moderate level of support (M=3.21, SD=0.58); interpersonal support was the strongest dimension (M=3.54, SD=0.62), while resource support was the weakest (M=2.87, SD=0.71), particularly in terms of access to specialized nutrition counseling and weight management-specific facilities. Correlation analysis confirmed positive relationships between environmental support systems, socio-psychological factors, and weight management effectiveness (r=0.38–0.57, p<0.001). Structural equation modeling revealed that environmental support systems had a direct positive effect on weight management effectiveness (β=0.28, p<0.001) and that self-efficacy (indirect effect=0.17, 95% CI=[0.12, 0.23]) and group norms (indirect effect=0.10, 95% CI=[0.05, 0.15]) served as significant mediators, while behavioral motivation did not exhibit a significant mediating role. Qualitative results complemented the quantitative findings, highlighting an uneven distribution of environmental support (strong coach and peer support alongside limited resource access), the role of self-efficacy as a key enabler of weight management behaviors, and the influence of team norms in either discouraging or normalizing risky rapid weight loss practices. This study enriches interdisciplinary research at the intersection of environmental psychology, sports psychology, and public health, while providing actionable implications for colleges and coaches to optimize weight management support strategies for student-athletes.